Peginterferon Alfa-2a plus Ribavirin in Japanese Patients Infected with Hepatitis C Virus Genotype 2 Who Failed Previous Interferon Therapy - Kanda, Tatsuo (Ivyspring International Publisher, 2012)
Some patients infected with hepatitis C virus (HCV) genotype 2 could be cured with treatment shorter than 24 weeks using peginterferon plus ribavirin, but there are still treatment-refractory patients. Direct-acting antivirals (DAAs) are not currently available for HCV genotype 2 patients, different from genotype 1 patients, in clinical practice. We investigated 29 HCV genotype 2-infected Japanese patients who had been previously treated and failed to clear HCV. We retreated them with peginterferon alfa-2a plus ribavirin and measured HCV RNA level to assess the efficacy and safety of this treatment in patients who had failed previous therapy. We found that retreatment of HCV genotype 2-infected Japanese patients with peginterferon alfa-2a plus ribavirin for 24-48 weeks led to 60 to 66.6% sustained virological response (SVR) in patients previously treated with (peg-)interferon monotherapy and to 69.9% SVR in relapsers previously treated with peginterferon plus ribavirin. Attention should be paid to certain patients with unique features. Selection of patients according to their previous treatment could lead to optimal therapy in HCV genotype 2 treatment-experienced patients.